Succeeding with standards : linking curriculum, assessment, and action planning - Carr, Judy F. (Association for Supervision and Curriculum Development, 2001)
How do you reshape the local curriculum to incorporate local, state, and national standards? Succeeding with Standards: Linking Curriculum, Assessment, and Action Planning offers a practical, school-tested solution to the challenge of incorporating standards at all levels with the best of the local education system. In this book, Judy Carr and Douglas Harris describe a comprehensive process by which schools and districts can turn piecemeal initiatives into a coherent plan. The authors share their extensive experience in schools across the United States, especially groundbreaking work in Vermont, to depict the standards-linking process. They explain how to . Determine who is to teach and assess each standard . Create a curriculum and assessment plan . Define effective practice . Create a comprehensive assessment system . Map out a path to success through action planning Improved student performance is the centerpiece of all standards-linking processes. Carr and Harris emphasize this point, clearly keeping Succeeding with Standards within the context of improving academic performance for all children. They also cover challenges related to reporting results and addressing professional development in a standards-based environment. Plentiful figures and examples highlight Carr and Harris's examples and advice. An extensive glossary and helpful list of selected resources round out the volume.